Carcinoma planoepitheliale of the vestibule of the nose and upper lip with aggressive course – case report - Bacharewicz, Joanna; Reduta, Teresa; Pawłoś, Anna; Chodynicka, Bożena; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Carcinoma planoepitheliale is a non-melanotic skin cancer with infiltrative growth that may metastasize most often to lymph nodes. The prognosis depends on localization, magnitude, depth of infiltration and histopathological type of tumour. Presence of metastases to lymph nodes decreases the cure index to less than 20%. Aggressive, unfavourable course is observed in elderly and immunosuppressed persons. Objective . Presentation of a case of squamous cell carcinoma of the vestibule of the nose with rapid, aggressive course and atypical appearance suggesting bacterial or fungal infection. Case report . A 53-year-old healthy male was admitted to the Department of Dermatology and Venereology due to a painful skin lesion in the vestibule of the nose lasting for one month. On admission an inflammatory, swollen, livid-red nodular lesion with presence of follicular pustules on the surface in the left nose vestibule and upper lip was observed. Histopathology revealed squamous cell carcinoma G2. At the diagnosis the tumour infiltrated the jaw bone and metastasis to the lymph node was found. Despite complex treatment fast progression of the neoplastic process was observed. Conclusions . Atypical clinical picture of cancer may delay the proper diagnosis and make the prognosis worse. All lesions with non-characteristic appearance resistant to therapy should be verified by histopathological examination.